Penggunaan Metode Card Sort untuk Meningkatkan Keaktifan Siswa pada Mata Pelajaran Pendidikan Agama Islam di SMPN 3 Gunung Tuleh - Nadia Afrina; Khapipah Khapipah; Kasmaniar Kasmaniar; Annisa Aulia Putri (Kampus Akademik Publiser, 2024)
This study was motivated by the low level of activity among eighth-grade students at SMP Negeri 03 Gunung Taleh in Islamic Religious Education (PAI) classes. Based on data from the even semester, 64% of students were still classified as inactive, while only 36% were active. This condition occurred because learning was still conventional and the methods used were ineffective. The purpose of this study was to increase student activity in IRE learning through the application of the card sort method. This study was a classroom action research (CAR) conducted in two cycles, each consisting of three meetings. The research subjects were 33 eighth-grade students at SMP Negeri 03 Gunung Taleh. The research procedure included planning, implementation of actions, observation, and reflection. Data were collected through observation, interviews, and documentation, then analyzed using qualitative and quantitative approaches. The results showed an increase in student activity after the application of the card sort method. In cycle I, the average student activity score was 51.49%, while in cycle II it increased to 71.23%. There was an increase of 19.74% from cycle I to cycle II. Thus, the application of the card sort method proved to be effective in increasing the activity of students in class VIII of SMP Negeri 03 Gunung Taleh in PAI learning.